Moon Girl and Devil Dinosaur. BFF. #5, Know how - Montclare, Brandon; Hadley, Amy Reeder, 1980- (Abdo Spotlight, 2018)
Lunella Lafayette is a preteen living in New York who happens to be a super-genius with an inhuman gene and an alter-ego known as Moon Girl. She hopes to use her intelligence to change the world alongside Devil Dinosaur, a red-scaled, prehistoric beast that slipped through a space-time portal from the past. But after the Hulk takes Devil Dinosaur into protective custody, Moon Girl must find a way to get him back.